BAP1 depletion in human B‐lymphoblast cells affects the production of innate immune cytokines and chemokines. (3rd November 2022) - Takagi‐Kimura, Misato; Tada, Akio; Kijima, Takashi; Kubo, Shuji; Ohmuraya, Masaki; Yoshikawa, Yoshie
Abstract: BRCA1 associated protein 1 (BAP1) is a ubiquitin C‐terminal hydrolase that deubiquitinates histone H2AK119ub and other proteins and regulates the expression of multiple genes. The knockout of this tumor suppressor gene results in severe thymic atrophy, complete loss of the T cell lineage, and abnormal B cell development in mice. In the current study, we investigated in vitro effects of BAP1 knockout on cytokine and chemokine production using the human B‐lymphoblast cell line TSCE5. We confirmed that knockout changed the production of innate immune‐associated genes and their receptors. The CCL19, CCR7, CCL2, and CXCR5 genes associated with T and B cell migration were upregulated. Knockout cells producing high levels of CCL19 showed acceleration of actin polymerization, which is essential for cell migration. CD69, PTPRC, and TLR3 genes that activate inflammation were downregulated. The tumor necrosis factor ligand genes TNF, LTA, and TNFSF10 were downregulated by knockout. In knockout cells, TNFα production was strongly downregulated upon the addition of H2 O2, but NF‐κB in the basal condition and when TNFα was added was augmented, suggesting that these cells could respond to TNFα. These results indicated that BAP1 affects the expression of chemokines and cytokines, T and B cell migration, and activated inflammation associating with innate immunity.